1983
DOI: 10.1007/bf00427969
|View full text |Cite
|
Sign up to set email alerts
|

Absence of central effects in man of the benzodiazepine antagonist Ro 15-1788

Abstract: The benzodiazepines are typified by a profile of side effects which includes drowsiness, ataxia and incoordination. Ro 15-1788, an imidazodiazepine derivative, exhibits marked antagonism of the behavioural and biochemical effects of the benzodiazepines in animals and man. It is devoid of any behavioural activity in animals, except at very high doses. In the present study the effects of single rising oral doses of Ro 15-1788 on cognitive, psychomotor and subjective function in man have been assessed using a bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
2
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 21 publications
4
15
2
1
Order By: Relevance
“…Flumazenil did not affect the risk assessment measures, but it dramatically potentiated flight reactions while weakly, albeit significantly, reducing defensive aggression and contextual anxiety. The effects of flumazenil on flight may well fit with clinical observations that the drug is somewhat anxiogenic in healthy volunteers (Darragh et al, 1983;Duka et al, 1986;Schopf et al, 1984) and that it increases the frequency of panic attacks in panic disorder patients (Maddock, 1998;Nutt et al, 1990;Woods et al, 1991). The weak agonist-like activity of flumazenil on defensive aggression is at first glance surprising, but it may fit with the idea that the drug can produce a GABA A -benzodiazepine receptor set point shift either toward the agonistic or the inverse agonistic direction, depending on the aversiveness of the situation (Belzung et al, 2000).…”
Section: Effects Of Nonselective Gaba a -Benzodiazepine Receptor Ligasupporting
confidence: 75%
“…Flumazenil did not affect the risk assessment measures, but it dramatically potentiated flight reactions while weakly, albeit significantly, reducing defensive aggression and contextual anxiety. The effects of flumazenil on flight may well fit with clinical observations that the drug is somewhat anxiogenic in healthy volunteers (Darragh et al, 1983;Duka et al, 1986;Schopf et al, 1984) and that it increases the frequency of panic attacks in panic disorder patients (Maddock, 1998;Nutt et al, 1990;Woods et al, 1991). The weak agonist-like activity of flumazenil on defensive aggression is at first glance surprising, but it may fit with the idea that the drug can produce a GABA A -benzodiazepine receptor set point shift either toward the agonistic or the inverse agonistic direction, depending on the aversiveness of the situation (Belzung et al, 2000).…”
Section: Effects Of Nonselective Gaba a -Benzodiazepine Receptor Ligasupporting
confidence: 75%
“…imipramine,¯uoxetine, moclobemide and phenelzine), reduced¯ight behavior [12,48,49,51]. In contrast, drug challenges known to trigger or potentiate human panic responses such as acute imipramine,¯uoxetine, yohimbine or the BZ receptor antagonist¯umazenil [27,54,55,90] were found to increase¯ight [16,48]. Also in agreement with clinical data are the ®ndings that the traditional BZ chlordiazepoxide, the 5-HT1A receptor agonist buspirone and the 5-HT2 receptor antagonist mianserin did not modify¯ight behavior in this test [50,52].…”
Section: Panic Disorder (Pd)supporting
confidence: 65%
“…For example, Sch6pf et al (1984) reported marked "stimulant-like" effects of Ro 15-1788 on the electroencephalogram (EEG) and reduction of N1P2 and P2N2 amplitudes of the averaged evoked response. Darragh et al (1983), whilst finding no behavioural effects on psychometric tests of oral doses of up to 600 mg Ro 15-1788, did report significant changes on subjective measures. Thus, although most human evidence has indicated that Ro 15-1788 is an effective benzodiazepine antagonist with apparently no marked intrinsic effects even at doses of up to 600 mg, it may possess some agonist as well as antagonist properties similar to other specific antagonists that act on different classes of receptors (see Jaffe and Clovet 1981 concerning opiate receptors).…”
mentioning
confidence: 67%